Cultivating Ethnographic Sensibilities in Ethnographies of Dying People. (28th August 2022) - Arteaga, Ignacia; Llewellyn, Henry
Abstract: Ethnographers engaged in fieldwork with people who are dying face particular demands concerning the nature and limits of their relationships. Drawing on case studies of two patients in the United Kingdom affected by ultimately fatal brain cancer and bowel cancer, we elaborate on the concept of ethnographic sensibility. We highlight the continual attunement of capacities that guide our participation in intersubjective encounters that are suffused by an "existential excess" and help make sense of rapid transformations in our relationships with those who are dying. We situate our approach to ethnographic sensibility within phenomenological notions of shared experience and social becoming to discuss some of the features and challenges of producing knowledge forms about the ends of life.